2014
DOI: 10.1016/j.niox.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nitrite bioactivation

Abstract: It is now accepted that the anion nitrite, once considered an inert oxidation product of nitric oxide (NO), contributes to hypoxic vasodilation, physiological blood pressure control, and redox signaling. As such, its application in therapeutics is being actively testing in pre-clinical models and in human phase I–II clinical trials. Major pathways for nitrite bioactivation involve its reduction to NO by members of the hemoglobin or molybdopterin family of proteins, or catalyzed dysproportionation. These conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 130 publications
1
123
0
3
Order By: Relevance
“…Therefore, because of its extended lifetime, its ability to resist nucleophilic attack, and its ability to release NO, ONSS − (in comparison with HSNO) seems to be a candidate as a NO transporter or extended NOreleasing species. The idea that biological NO sources exist (besides direct NOS generation) with targeted release at distant sites or extended kinetics is not new (8,9), but ONSS − appears to be a viable candidate for this role.…”
Section: Integrated View Of Small Molecule Signalingmentioning
confidence: 99%
“…Therefore, because of its extended lifetime, its ability to resist nucleophilic attack, and its ability to release NO, ONSS − (in comparison with HSNO) seems to be a candidate as a NO transporter or extended NOreleasing species. The idea that biological NO sources exist (besides direct NOS generation) with targeted release at distant sites or extended kinetics is not new (8,9), but ONSS − appears to be a viable candidate for this role.…”
Section: Integrated View Of Small Molecule Signalingmentioning
confidence: 99%
“…Аналогічно реверсному спряженому (de novo синтез NO)/ неспряженому(генерація • О 2 -) стану сNOS, працює ще один потужний генератор як синтезу NO так і • О 2 --реверсний фермент ксантиноксидаза, він же одночасно нітрат-і нітритредуктаза. Давно відкритий цей феномен ксантиноксидази останнім часом став широко досліджуватися саме в цьому аспекті [18][19][20][21]. Неважко припустити, що і реверсний процес неспряження cNOS, за якого також дуже швидко можна підвищити вміст NO і, навпаки, зменшити утворення • О 2 -, теж має бути доступним для багатьох фізіологічних біорегуляторів.…”
Section: результати та їх обговоренняunclassified
“…A surprisingly large number of different proteins have been identified that can reduce nitrite to NO in vitro, and detailed recent reviews on this topic are available (van Faassen et al, 2009;Kapil et al, 2010b;Lundberg & Weitzberg, 2010;Kim-Shapiro & Gladwin, 2013). However, there is neither agreement in the literature as to which of these potential nitrite bioactivation processes are the most relevant for vasodilatation (or any other biological process), nor do we understand the reason for this particularly high degree of redundancy.…”
Section: Mechanisms Of Nitrite-mediated Vasodilatationmentioning
confidence: 99%
“…According to this principle, the proteins involved in nitrite reduction can be divided into two broad groups: heme-based proteins and molybdopterin-based oxidoreductases. The two best studied examples of the former are Hb and Mb, and both have been claimed to play major roles in nitrite bioactivation (Shiva et al, 2007a;Totzeck et al, 2012b;Kim-Shapiro & Gladwin, 2013), in particular under hypoxic conditions (Crawford et al, 2006;Hendgen-Cotta et al, 2014). Less well studied members of this group include neuroglobin and cytoglobin, cytochrome C and cytochrome C reductase, cytochrome P450, and the endothelial NOS isoform.…”
Section: Mechanisms Of Nitrite-mediated Vasodilatationmentioning
confidence: 99%